A escola entre-vista: uma análise das interdependências entre a Escola Estadual Professor João José da Costa e o bairro da Torre (1984-2019) - Oliveira, Juliana Barros de (2020)
When we studying the urban space, the neighborhood appears as a kind of microspace that integrates with the city, being understood as a place where social life takes place. This place is part of the urban layout of a location where a school is often inlaid, an institution that, in turn, plays a fundamental role, with regard to formal education. In addition to being perceived in the condition of urban equipment inserted in a community, the school is capable of producing a culture that is its own, as emphasized by Julia (2001), in addition to establishing, in the neighborhood, interdependencies, in the perspective advocated by Elias (2008), featuring a figuration, as occurs between the State School of Fudamental and High School Professor João José da Costa and the neighborhood of Torre. In this relationship between neighborhood and school and school and neighborhood, figures are expressed in which individuals occupy alternating functions, in which these places form a locus of learning, in addition to presenting themselves as true anchors of the memory of individuals who establish relationships in both spaces. The general objective of this thesis is to analyze the existing interdependencies between the Professor João José da Costa School and the Torre neighborhood, in view of the need to unveil elements that compose these relationships and form a figuration that includes the school and the neighborhood. For this purpose, as oral sources to compose the analysis, oral reports from the interviewees who had experiences in school and neighborhood spaces, as well as newspapers, iconography (plants, maps and photographs) in addition to sources produced by the school and about the school and the neighborhood. The analysis and interpretation of such sources joined the Eliasian theoretical-methodological framework used to compose the thesis, which developed when crossing categories that emerged from the sources themselves, such as place, time and architectural space, successively encompassing them in the constitution of the sections that make up the study. The interdependence relations observed between school and neighborhood determine the figurations existing in these places, observing them in the light of the Eliasian theory, as well as basing ourselves, in this understanding, on the contributions of Portelli (1997) (2000), when observing the interview in the condition of experiment between interviewer and interviewee. In view of the analyzes carried out, there is a school and a neighborhood perceived as places of learning, established beyond the limits of its materiality and reconstituted through the memory of the interviewees.